Emerging societies coexistence of childhood malnutrition and obesity - Kalhan, Satish C.; Prentice, Andrew M.; Yajnik, Chittaranjan S. (Nestlé nutrition workshop series. Pediatric program, 2009)
In many developing and emerging societies, the coexistence of malnutrition and obesity is becoming increasingly prevalent. Caused by a rapid change in terms of economic growth and increased availability of food, the main challenge of this nutrition transition is the balance between short-term benefits and long-term risks of increased metabolic diseases.The publication at hand starts with an epidemiological overview, including regional case studies from India, China and Africa. This is followed by an in-depth evaluation of the phenomenon, focussing on the origin and prevalence of malnutrition and its link to obesity, the possible mechanisms of metabolic injury, and the strategies for preventing the projected epidemic of non-communicable disease. Also stressed is the need for further research to determine which population segments should be targeted at what stages of their lifecycle in order to achieve optimal results.Written by an international panel of experts, this volume will be of particular value for pediatricians, perinatologists, obstetricians, endocrinologists, public health scientists and epidemiologists